An aqueous Commiphora myrrha extract ameliorates paclitaxel-induced peripheral neuropathic pain in mice - Al-Romaiyan, Altaf; Barakat, Ahmad; Jose, Liny; Masocha, Willias (Frontiers in Pharmacology, 2023)
Background: Chemotherapy-induced neuropathic pain (CINP) is a debilitating side effect in individuals undergoing cancer treatment. Treatment of CINP with the current available classes of drugs is limited and often with unsatisfactory results. Finding therapeutic alternatives of plant origin could provide a new way for the management of CINP. Commiphora myrrha (CM) resin extract has been reported to have anti-inflammatory and analgesic activities but the effect of CM on neuropathic pain is yet to be investigated in CINP. Objective: The aim of this study was to investigate the antinociceptive effect of CM extract in a mouse model of paclitaxel-induced neuropathic pain (PINP). Methods: The effects of CM on thermal hyperalgesia and mechanical allodynia were assessed in female BALB/c mice with PINP using hot plate and plantar aesthesiometer, respectively. Motor coordination was evaluated using rotarod apparatus. The involvement of TRPV1 channels in CM actions was investigated using capsaicin (a TRPV1 agonist)-induced nociception test. The genetic expression was assessed by real time PCR, while protein expression was assessed by Wes™. Results: Administration of CM to mice with established PINP produced a dose-dependent reduction in thermal hyperalgesia. Prophylactic treatment of mice with CM prevented the development of paclitaxel-induced thermal hyperalgesia and mechanical allodynia. CM did not change motor coordination of mice. CM significantly decreased the number and duration of the flick responses following capsaicin test. The protein expression of TRPV1 was increased in the spinal cord of paclitaxel-treated animals compared to control animals, while CM-treated animals had values similar to control animals. The mRNA expression of Nrf2, a major antioxidant transcription factor, was increased in paw skin of mice treated with CM as compared to paclitaxel alone. Conclusion: These results indicate that CM may both treat established and prevent the development of paclitaxel-induced thermal hyperalgesia and mechanical allodynia without any impairment in the motor activity of mice. CM may mediate its action through peripheral inhibition of TRPV1 channels activity, restoration of normal TRPV1 protein expression in the spinal cord, and elevation of cellular antioxidant defenses. CM has the potential to be used as a therapeutic alternative to treat CINP.